2009
DOI: 10.1103/physrevlett.102.175506
|View full text |Cite
|
Sign up to set email alerts
|

Superhard Monoclinic Polymorph of Carbon

Abstract: We report a novel phase of carbon possessing a monoclinic C2/m structure (8 atoms/cell) identified using an ab initio evolutionary structural search. This polymorph, which we call M-carbon, is related to the (2x1) reconstruction of the (111) surface of diamond and can also be viewed as a distorted (through sliding and buckling of the sheets) form of graphite. It is stable over cold-compressed graphite above 13.4 GPa. The simulated x-ray diffraction pattern and near K-edge spectroscopy are in satisfactory agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
329
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 526 publications
(356 citation statements)
references
References 30 publications
24
329
3
Order By: Relevance
“…When graphite is compressed under ambient temperature, x-ray IXS experiments showed that it undergoes a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 transition at 17 GPa, where half of the π-bonds between graphite layers convert to σ-bonds, whereas the other half remain as π-bonds in the HP form [72]. The HP form has a distorted Mcarbon structure [661] and is super hard, capable of indenting cubic-diamond single crystals. Similarly, compressing fullerenes causes crushed C60 cages, forming superhard forms of carbon that are quenchable to ambient pressure [422,662].…”
Section: Superhard Materialsmentioning
confidence: 99%
“…When graphite is compressed under ambient temperature, x-ray IXS experiments showed that it undergoes a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 transition at 17 GPa, where half of the π-bonds between graphite layers convert to σ-bonds, whereas the other half remain as π-bonds in the HP form [72]. The HP form has a distorted Mcarbon structure [661] and is super hard, capable of indenting cubic-diamond single crystals. Similarly, compressing fullerenes causes crushed C60 cages, forming superhard forms of carbon that are quenchable to ambient pressure [422,662].…”
Section: Superhard Materialsmentioning
confidence: 99%
“…XAS and EELS of graphene has been computed previously using density functional theory (DFT) implemented for ground-state electronic structure calculations [5,6]. These methods usually rely on periodic boundary conditions so that the asymptotic behavior of wavefunction may be not reproduced well for low-dimensional systems in particular directions, and use fixed basis sets whose convergence for high energy states may be problematic.…”
Section: Introductionmentioning
confidence: 99%
“…33 However, Mao et al find cold-compressing graphite leads to new superhard carbon allotropes differing from diamond. 34 A few candidates including R and P carbon, 20 bct C 4 , 26 W-C, 35 M-C, 36 and Z-C 37 have been proposed to match with the experimental results. Compressing CNTs yields more interesting but perplexing phases owing to the structural complexity of CNTs, such as chirality, diameter, single-wall or multi-wall.…”
Section: Introductionmentioning
confidence: 65%